TEACHING THE SUBJECT OF RELIGION IN MODERN UZBEKISTAN: REPRESENTATION OF CULTURE IN EDUCATION - Ashurov N. B. (European Science Publishing, 2024)
The article discusses the teaching of the subject religion in modern Uzbekistan, the representation of culture in education.
Keywords: religion, Uzbekistan, subject, culture, education, young generation, value.